The Application of Psycholinguistic Principles to the study of Bilingual Learning (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This thesis explores the effectiveness of different psycholinguistic characteristics. The global trend toward economic, political, and cultural integration recognizes bilingual education as one of the key components of language education. Thus, psycholinguistic methods are required for foreign language instruction. "The science of what mental processes take part in, when we generate speech, i.e. speak, listen, and read, as well as how we master speech in our native language and in a foreign language" is how R.F. Frumkina (2004) defines psycholinguistics. The technique's ability to create these skills will increase with the amount of knowledge about an individual's speaking behavior. Finding linguistic and psycholinguistic solutions to the interrelationship issues in bilingual education is the goal of the article. The article's structure contains a description of the characteristics of contemporary psycholinguistic techniques in bilingual education settings.